Tie heterogeneity in networks of interlocking directorates: a cost–benefit approach to firms' tie choice - Julia Brennecke; Olaf N. Rank (Business Research, 2017)
This conceptual paper investigates the creation of interlocking directorate ties focusing on firms' choice between sent, received, and undirected board interlocks. Drawing on a framework on the benefits of board interlocks stemming from resource dependence theory, we synthesize prior research on the consequences of interlocks and demonstrate that each type of interlock goes along with unique knowledge-based, social influence-related, and institutional benefits and costs. We frame tie choice as a strategic decision based on a cost-benefit analysis and suggest that the tie-specific benefits and costs lead to the three types of ties not being equal alternatives. Appealing to specific motives for tie creation, these benefits and costs influence firms' choice between the three types of interlocks. Our synthesis and cost-benefit analysis contribute to prior research by shedding light on the role of tie heterogeneity as a driver of tie creation as opposed to a factor causing firm-level outcomes. By focusing on content of ties, we extend the typically purely structural research on interlocking directorate networks. We suggest directions for future research and discuss possibilities to empirically validate our propositions on how tie-specific opportunities and constraints will affect tie choice.
Keywords: D85; G30; L14; M10; 650; Interlocking directorates; Tie creation; Tie content; Resource dependence theory; Cost-benefit analysis